Voltage transient analysis as a generic tool for solar junction characterization - Prakoso, Ari Bimo (2020)
Surface photovoltage transients on solar junctions have often been associated with carrier lifetime in the literature. However, the carrier decay in a junction is not governed by a first order carrier decay, but resulting from a differential capacitance interacting with a differential conductivity. This phenomenon is well known as the Kane-Swanson formalism in an engineering context where the carrier density transient is measured by photoconductance with a microwave or infrared beam. In this work, we solve the same differential equations numerically to model the carrier decay in the large signal domain extending over five orders of carrier density. Since the surface voltage is linked to the carrier density by a logarithmic relation, we express the carrier decay as surface photovoltage transients. We show how from photovoltage transients, the same information as from photoconductance can be drawn. To demonstrate the method as a generic tool, it is applied to four types of solar cells, two monocrystalline silicon cells, a Perovskite solar cell, a transition metal oxide/silicon hybrid junction, and a CIGS solar cell. Acquiring photovoltage transients by Kelvin force microscopy allows working on partial junctions without top contact, speeding up research of future photovoltaic materials. Furthermore, parameters may be mapped with a better lateral resolution compared to microwave photoconductance.